2018
DOI: 10.1371/journal.pone.0196117
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a neutrophil-related gene expression signature that is enriched in adult systemic lupus erythematosus patients with active nephritis: Clinical/pathologic associations and etiologic mechanisms

Abstract: Both a lack of biomarkers and relatively ineffective treatments constitute impediments to management of lupus nephritis (LN). Here we used gene expression microarrays to contrast the transcriptomic profiles of active SLE patients with and without LN to identify potential biomarkers for this condition. RNA isolated from whole peripheral blood of active SLE patients was used for transcriptomic profiling and the data analyzed by linear modeling, with corrections for multiple testing. Results were validated in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 40 publications
2
39
0
Order By: Relevance
“…For this purpose, we first analyzed a set of genes defined as a neutrophil-related signature in the different breast cancer subtypes. These neutrophil-related genes ( MPO , DEFA1B , MMP8 , CEACAM8 , LTF , and DEFA4 ) were identified and evaluated in a previous study [ 39 ]. The MPO gene encodes myeloperoxidase, an abundant enzyme in the neutrophil azurophilic granules, which has microbicidal activity through the generation of hypochlorous acid [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, we first analyzed a set of genes defined as a neutrophil-related signature in the different breast cancer subtypes. These neutrophil-related genes ( MPO , DEFA1B , MMP8 , CEACAM8 , LTF , and DEFA4 ) were identified and evaluated in a previous study [ 39 ]. The MPO gene encodes myeloperoxidase, an abundant enzyme in the neutrophil azurophilic granules, which has microbicidal activity through the generation of hypochlorous acid [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The role of IL17A in regulating granulopoiesis and neutrophil recruitment via induction of G-CSF is well recognized under homeostatic conditions 34,70 and a few studies have identified IL17-A as important for neutrophil recruitment to the sites of sterile inflammation 71,72 . In lupus, elevated IL-17A expression is found in cutaneous lesions 73,74 and increased circulating IL-17A levels have been associated with worse disease manifestations 75,76 , although the specific relationship to neutrophils, a pathogenic population in this disease, 11,[15][16][17] remains unexplored. Besides its direct effects on G-CSF-mediated mobilization of neutrophils from the bone marrow, IL-17A may also contribute to neutrophil homing to the kidney by stimulating expression of adhesion molecules (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils can also promote tissue repair by phagocytosis of cellular debris and by enabling tissue revascularization 50 . In SLE, a neutrophil gene signature is a strong predictor of active disease including LN and cutaneous lupus [15][16][17] . Neutrophils are found in cutaneous lesions [10][11][12] as well as kidney biopsy specimens 13,14 of SLE patients and their inflammatory properties have been attributed to NET formation 14,21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations